2007
DOI: 10.1161/01.hyp.0000252431.75154.3a
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Low-Normal Blood Pressure and Kidney Disease in Type 1 Diabetes

Abstract: Abstract-Current recommendations, largely based on studies in type 2 diabetes, suggest lower target blood pressures (BPs) for individuals with diabetes than for the general population. However, the effect of lower BP on renal outcomes in type 1 diabetes is uncertain. In a population-based cohort of type 1 diabetes adults (mean age: 33.1 years) based in Wisconsin, of which the distribution of baseline BP was in the low-normal range, we examined the relationship between decreasing categories of systolic and dias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
0
11
0
1
Order By: Relevance
“…77 Lowering BP further may improve target organ measures (cIMT, left ventricular mass, proteinuria), 187,188 but the risk of a drop in diastolic BP to <60 mm Hg, 189 a level that may impair coronary filling, has led the ADA to suggest avoiding hypotension. 56 No pediatric longitudinal studies with hard cardiovascular events are available; however, evidence for target organ damage in youth with diabetes mellitus 102,114,190 led to the recognition that children with either T1DM or T2DM are at elevated risk of developing atherosclerotic CVD before 30 years of age.…”
Section: Blood Pressurementioning
confidence: 99%
“…77 Lowering BP further may improve target organ measures (cIMT, left ventricular mass, proteinuria), 187,188 but the risk of a drop in diastolic BP to <60 mm Hg, 189 a level that may impair coronary filling, has led the ADA to suggest avoiding hypotension. 56 No pediatric longitudinal studies with hard cardiovascular events are available; however, evidence for target organ damage in youth with diabetes mellitus 102,114,190 led to the recognition that children with either T1DM or T2DM are at elevated risk of developing atherosclerotic CVD before 30 years of age.…”
Section: Blood Pressurementioning
confidence: 99%
“…Prior prospective cohort studies (7,8) of patients with type 1 diabetes suggested that lower BP levels (<110–120/70–80 mmHg) at baseline entry were associated with a lower risk of adverse renal outcomes, including incident microalbuminuria. In one trial of antihypertensive treatment in type 1 diabetes (9), assignment to a lower mean arterial pressure (MAP) target of <92 mmHg (corresponding to ∼125/75 mmHg) led to a significant reduction in proteinuria compared with a MAP target of 100–107 mmHg (corresponding to ∼130–140/85–90 mmHg).…”
Section: Introductionmentioning
confidence: 99%
“…The strict control of blood glucose, as quickly as possible, was shown to be effective in major clinical trials [3, 4]. Blood pressure control has also been shown to be of major importance in many studies [57]. In addition, in patients who develop increased urinary albumin-creatinine ratio (ACR) levels, one or more of the medications that inhibit the renin-angiotensin-aldosterone system (RAAS) axis should be used to lower ACR levels [8, 9].…”
Section: Introductionmentioning
confidence: 99%